The analysis and monitoring of atmospheric volatile organic compounds via thermal desorption gas chromatography mass spectrometry - Wong, Gwendeline Kee Shien (2014)
An analytical method has been established for the quantitative determination of 48 gaseous volatile organic compounds (VOCs) that were detected in the outdoor environment in Western Singapore by Thermal Desorption Gas Chromatography Mass Spectrometry (TD-GCMS). Tenax/Carbopack X multi-sorbent tubes were evaluated for active sampling performance and the method was validated using VOC standard solutions. The procedure exhibited repeatability with relative standard deviation (%RSD) values ≤ 10%, linearity with R2 values ≥ 0.99 for concentrations from 0.02 to 500 ng, VOC standards breakthrough ≤ 5% , tube desorption efficiencies ~100% and the majority of recoveries were between 61% to 120%. 30 mL/min flow rate coupled with sampling volumes of 1 L and 5 L gave the best results for sampling breakthrough and reproducibility during air sampling. Most of the target analytes exhibited acceptable breakthrough ≤ 5%, reproducibility ≤ 20% and method detection limits below 0.5 ppbv. The analyte exceptions were pyridine that remained undetected during sampling experiments and dichloromethane that failed the breakthrough requirement.